The design and implementation of Arabic Speech Proficiency (Kalam) lectures is student-centered - Salih Yousif Sharaf Mohamed; Alimuddin Rivai (Language Development Center, 2023)
Background: Student-centered Arabic-speaking learning (Kalam) is important to be carefully and precisely designed so that Arabic learning is easier and more enjoyable according to the needs of students. Purpose: This study aims to present the concept design, implementation, and experimentation of the teaching and learning process of Arabic speaking proficiency centered on the needs of students through intensive training programs. Method: This type of research uses quasi-experimental experiments with a control group pretest-posttest design. The population of this study is even semester 2022-2023 students totaling 205 students and a sample of 35 students. The sampling technique uses random sampling from class III-A and III-B units. Data collection techniques are observation, experimentation, interviews, and documentation. Data analysis in this study was carried out repeatedly with a data reduction system, data presentation, and verification of conclusions. Results and Discussion: The design and implementation of speaking skills a very important skills in learning foreign languages, but to obtain maximum results, the lecturers' ability techniques and methods used are determining factors in achieving an increase in student speaking proficiency. The calculation results showed that the effectiveness rate and difference in students' Kalam skills was 83.13%, and the use of student-centered active speaking methods did not experience significant obstacles, which was an average of 9.52%, this showed that the intensive Arabic training program was very effective in learning and improving proficiency (Kalam). Conclusions and Implications: The design and implementation of lectures are more effectively carried out by being student-centered through brainstorming. The formulation of learning targets by individual students implements lectures more student-centered. It takes Takrar, tazawudd, and ta'awwun techniques to develop Arabic speaking skills in a continuous intensive program. This research implies that the application of Kalam learning patterns through training intensity programs is very well carried out gradually and continuously So that the material that has been designed can be developed with actual themes according to the needs of students.